Neural Androgen Synthesis and Aggression: Insights From a Seasonally Breeding Rodent - Munley, Kathleen M.; Rendon, Nikki M.; Demas, Gregory E. (Frontiers in Endocrinology, 2018)
Aggression is an essential social behavior that promotes survival and reproductive fitness across animal systems. While research on the neuroendocrine mechanisms underlying this complex behavior has traditionally focused on the classic neuroendocrine model, in which circulating gonadal steroids are transported to the brain and directly mediate neural circuits relevant to aggression, recent studies have suggested that this paradigm is oversimplified. Work on seasonally-breeding mammals that exhibit territorial aggression outside of the breeding season, such as Siberian hamsters (Phodopus sungorus), has been particularly useful in elucidating alternate mechanisms. These animals display elevated levels of aggression during the non-breeding season, in spite of gonadal regression and reduced levels of circulating androgens. Our laboratory has provided considerable evidence that the adrenal hormone precursor dehydroepiandrosterone (DHEA) is important in maintaining aggression in both male and female Siberian hamsters during the non-breeding season, a mechanism that appears to be evolutionarily-conserved in some seasonally-breeding rodent and avian species. This review will discuss research on the neuroendocrine mechanisms of aggression in Siberian hamsters, a species that displays robust neural, physiological, and behavioral changes on a seasonal basis. Furthermore, we will address how these findings support a novel neuroendocrine pathway for territorial aggression in seasonally-breeding animals, in which adrenal DHEA likely serves as an essential precursor for neural androgen synthesis during the non-breeding season.